SINERGI PENGAWAS DAN KEPALA SEKOLAH DALAM PENCAPAIAN STANDAR KINERJA GURU PENDIDIKAN AGAMA ISLAM - Nurhikmah Nurhikmah; Muhaemin Muhaemin; Hilal Mahmud (Institut Agama Islam Negeri (IAIN) Palopo, 2023)
The synergy of supervisors and principals has an influence on the performance of Islamic religious education teachers. The synergy of supervisors and principals not only has advantages in helping teachers but also has disadvantages that need to be corrected. This study aims to identify forms of synergy carried out by supervisors and school principals in making work programs, supervising and carrying out performance appraisals. Knowing the internal and external factors that impede the synergy of supervisors and principals in achieving PAI teacher performance standards and describing the achievement of PAI teacher performance standards. This research is a descriptive qualitative research with a qualitative approach. Data obtained through observation, interviews and documentation. The results of this study indicate that: first, the form of synergy that is carried out in making work programs is by holding joint deliberations. Then class visits are used in conducting supervision. Furthermore, the implementation of performance appraisal is carried out using the Field review method. Second, internal and external factors show that the low ability and work ethic of teachers is caused by the location of the school which is quite far from the supervisor, the supervisor is unable to come and the funds are minimal and external factors such as government policies that change frequently. Third, the achievement of PAi teacher performance standards is good as evidenced by the achievements of students in the religious field.